2012
DOI: 10.1177/0333102412445223
|View full text |Cite
|
Sign up to set email alerts
|

Hypnic headache: Response to lamotrigine in two cases

Abstract: To our knowledge, the response to lamotrigine in HH cases has never been reported. Because of its safety profile and availability, lamotrigine can be an effective alternative treatment in HH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…4 Lamotrigine (LTG) is the most effective prophylaxis in SUNCT and it has been also reported to be effective in two patients with HH at the dose of 50 and 75 mg/day. 10 In our patient, LTG was clearly effective at the dosage of 100 mg/day. When HH developed, the patient was already receiving LTG 100 mg/day.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…4 Lamotrigine (LTG) is the most effective prophylaxis in SUNCT and it has been also reported to be effective in two patients with HH at the dose of 50 and 75 mg/day. 10 In our patient, LTG was clearly effective at the dosage of 100 mg/day. When HH developed, the patient was already receiving LTG 100 mg/day.…”
Section: Discussionsupporting
confidence: 52%
“…Caffeine is the drug of choice in HH and it is also effective when HH develops with other primary headaches . Lamotrigine (LTG) is the most effective prophylaxis in SUNCT and it has been also reported to be effective in two patients with HH at the dose of 50 and 75 mg/day . In our patient, LTG was clearly effective at the dosage of 100 mg/day.…”
Section: Discussionsupporting
confidence: 50%
“…Other medications that were not tried in our study, but have shown some effectiveness in case reports are onabotulinumtoxinA, hypnotics (doxylamine succinate, diphenhydramine, eszopiclone), and lamotrigine …”
Section: Treatment Optionsmentioning
confidence: 92%
“…Other medications that were not tried in our study, but have shown some effectiveness in case reports are onabotulinumtoxinA, 36 hypnotics (doxylamine succinate, diphenhydramine, eszopiclone), 37 and lamotrigine. 38 In light of the above, we feel that caffeine is a reasonable first line treatment option for HH, due to ease of use and a more benign side effect profile than any of the prescription medications, including lithium.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Among the many reported cases of HH, some had type 2 diabetes mellitus as co‐morbidity . However, in none of these patients was hypoglycemia responsible for the onset of pain.…”
Section: Discussionmentioning
confidence: 99%